PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TINDAKAN PAJAK AGRESIF (Studi pada Perusahaan Pertambangan yang Terdaftar di BEI 2011-2013) - Seprini '; Azwir Nasir; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to find out and analyze the effect of good corporate governance and corporate social responsibility on tax aggressivenss. The good corporate governance is proxied by size of board commissioners, managerial ownership, audit committee meetings, audit quality. Then at least, corporate social responsibility variable. This study uses secondary data with 51 mining companies sample listed in Indonesia Stock Exchange for three periods (2011-2013). The sampling technique used is purposive sampling analysis. The analytical method used is multiple regression by using SPSS 20. Based on the results of hypothesis testing found that The good corporate governance is proxied by size of board commissioners, managerial ownership, audit committee meetings, audit quality affect and significant on tax aggressiveness. And then corporate social responsibility affect and significant on tax aggressiveness. Adjusted score R square is 0.442 means 44.2% independent variable on this study be able to give an effect on dependent variable, and the left 55.8% is explained by other variable that’s not entered on this study.KeywordS : Good Corporate Governance, Corporate Social Responsibility, and Tax Aggressiveness